Digestion of Intact Gluten Proteins by Bifidobacterium Species: Reduction of Cytotoxicity and Proinflammatory Responses - De Almeida, Natália Ellen Castilho; Esteves, Franciele Grego [UNESP]; Dos Santos-Pinto, José Roberto Aparecido [UNESP]; Peres De Paula, Carla; Da Cunha, Anderson Ferreira; Malavazi, Iran; Palma, Mario Sergio [UNESP]; Rodrigues-Filho, Edson (American Chemical Society (ACS), 2020)
Celiac disease (CD) is a chronic illness characterized by an inflammatory process triggered by gluten protein intake. Recent evidence has suggested that the lower relative abundance of bifidobacteria in the intestinal lumen may be associated with CD. Herein, we assessed the effect of the Bifidobacterium species Bifidobacterium bifidum, Bifidobacterium longum, Bembidion breve, Bifidobacterium animalis alone, and also a Bifidobacterium consortium on the digestion of intact gluten proteins (gliadins and glutenins) and the associated immunomodulatory responses elicited by the resulting peptides. The cytotoxicity and proinflammatory responses were evaluated through the activation of NF-kB p65 and the expression of cytokines TNF-α and IL-1β in Caco-2 cell cultures exposed to gluten-derived peptides. The peptides induced a clear reduction in cytotoxic responses and proinflammatory marker levels compared to the gluten fragments generated during noninoculated gastrointestinal digestion. These results highlight the possible use of probiotics based on bifidobacteria as a prospective treatment for CD.
Keywords: bifidobacteria; celiac disease; gluten proteins; gluten-derived peptides; immunomodulatory response; toxicity